Implications of hypocobalaminemia as a negative prognostic marker in juvenile dogs with parvovirus enteritis - Luckschander-Zeller, Nicole; Giani, Bettina; Doulidis, Pavlos G.; Plickert, Hanna D.; Tichy, Alexander; Marculescu, Rodrig; Schwendenwein, Ilse; Burgener, Iwan A. (Frontiers in Veterinary Science, 2024)
Canine Parvovirus 2 (CPV-2) infection poses a significant global health risk to susceptible dogs. Hypocobalaminemia, defined as reduced serum cobalamin (CBL) concentrations, is a recognized complication in chronic enteropathies in adult dogs but remains poorly understood in the context of acute enteropathies, especially in young dogs. The aim of this study was to investigate the frequency and severity of hypocobalaminemia in young dogs with parvovirus enteritis and evaluation of CBL as a predictor of outcome. Thirty client-owned dogs diagnosed with parvovirus infection and thirty healthy controls were enrolled. Clinical, hematological, and biochemical tests, including CBL and serum methylmalonic acid (MMA) concentrations, were assessed. Results indicated a significantly higher prevalence of hypocobalaminemia in dogs with parvovirus enteritis compared to healthy controls, as well as a significant correlation with a disease severity score. Moreover, survivors demonstrated higher CBL concentrations than non-survivors, suggesting an eventual prognostic value of CBL status.However, parenteral CBL supplementation showed no significant effect on serum CBL or MMA concentrations, highlighting potential challenges in CBL uptake at the cellular level.Hypocobalaminemia in this population is caused by multiple factors such as reduced nutritional absorption, gastrointestinal losses, and increased metabolic demands. Further research is needed to develop tailored management strategies, evaluate the effectiveness of CBL supplementation, and understand the mechanisms behind hypocobalaminemia in parvovirus infection.